TINJAUAN PUSTAKA SISTEMATIS: KARAKTERISASI KEANEKARAGAMAN GENETIK SPESIES JERUK (Citrus sp.) MENGGUNAKAN PENANDA SIMPLE SEQUENCE REPEAT (SSR) - Oktaviana, Eryka; Setiati, Ning; Anggraito, Yustinus Ulung (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: The biodiversity of citrus plants is very abundant and many are cultivated, creating various types. However, the high demand makes orange farmers feel overwhelmed. This is what causes some orange cultivars to become rare. Characterization of the genetic diversity of citrus germplasm at the molecular level is an important and crucial step that can assist in the breeding and conservation process. The aim of this literature review is to provide information regarding molecular markers regarding the application of SSR molecular markers to analyze the genetic diversity of citrus. Method: The method used is a systematic literature review with the literature sources used coming from articles taken from national journals and international journals indexed by Scopus. Results: The application of molecular markers using the SSR method is useful for identifying and characterizing the genetic diversity of citrus germplasm so that it can assist in breeding and conservation actions. SSR has many advantages both in terms of its use and the results obtained. Conclusion: One application of molecular markers is to analyze plant genetic diversity. Simple Sequence Repeat (SSR) molecular markers can help to analyze the characteristics and genetic diversity of oranges so that they can assist in plant breeding and conservation purposes.